Integrating science & technology into development policies : (Organisation for Economic Co-operation and Development, 2007)
Science and Technology is a key driver of economic growth, and it may also help provide answers for managing resources and reducing pollution, addressing climate change and preserving biodiversity, as well as reducing disease and safeguarding health and well-being, while maintaining the general quality of life. This publication provides the proceedings of an international workshop, held in South Africa, intended to address how international co-operation in science and technology can further the three inter-related aspects (economic, social and environmental) of the development process. The workshop focused on good practices in international S T partnerships, specifically in the areas of water and energy.